The Eeffect of Cronobacter sakazakii on the Brains of Newborn Mice - adil, Hayder A. Al-Mandalawii; Estabraq A. Mahmoud (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Fifteenth of Cronobacter sakazakii were obtained from previous studies isolates were (infant formula, spinal fluid and bloods). The newborn mice and number was 15 obtaining healthy newborn mice from the Iraqi Center for Cancer and Medical Genetics whose ages ranged between 10-17 days and their weights 8.5 ± 1.25 gm, were divided into 3 groups. The samples were cut and placed in formalin, then placed in stabilizer and concentrations of alcohol (70%, 80%, 90%,100%) to complete dehydration after they were leached with xylene, embedded the samples paraffin wax (58°C) and sectioning the with thickness (5) micrometer and stained with Haematoxylin and Eosin stain. The results of an increase in the weight of the brain organ for the mice compared to the control treatment and this increase was significant at the probability level p≤0.05 and the results showed the inflammatory response of the brain of large number of polymorphnuclear cells and mononuclear cells as well as congested blood vessels with an increase in the size of endothelial cells. The presence of bleeding congestion and shrinking of nerve cells in the area of the cerebral cortex, gliosis (neuroma), was more prominent in the molecular layer in the brain of the newborn mice fed at a concentration of 105 cells and the occurrence of oedema ,the presence of haemorrhage in both concentrations of dosed newborn mice and necrosis of the choroid plexus concentration103 and 105 cells.